Polisi harga padi sebagai langkah meningkatkan pendapatan petani - Jaafar, Ahmad Sobri (Universiti Utara Malaysia, 1989)
The introduction of various price and subsidy schemes since 1949 and overall increased in productivity have, to an extent, improved the economic status of padi planters. Increases in the cost of production have, however, eroded the margin between minimum price and costs. Uneconomic land ownership patterns also present a problem in raising productivity. Both problems should be given consideration in formulating future pricing policies.